A comparison of design practice of bored piles/drilled shafts between Europe and North America. Issue 2 (2nd July 2016) - Brown, D.; Wulleman, T.; Bottiau, M.
Abstract : This paper assesses the comparative practices between Europe and North America with respect to the design of bored pile/drilled shaft foundations. Several major trends are identified that are common to both regions: (1) increasing complexity in the project demands and applications, and (2) more stringent testing and quality assurance requirements. The design codes differ in some respects but the most striking similarity between the European Union (EU) and the United States is the tendency for local (or national in the case of the EU) variations to persist in the implementation of design practices. Some of the variations reflect geologic differences, but much of the inconsistencies in design practice appear to be artefacts of the evolution of local practice that are not easily relinquished. Other common issues identified in the study include the wide local variations in constructability concerns with respect to concrete mix characteristics, reinforcement details and the influence of construction techniques on foundation performance.